The illustrated history of guns from first firearms to semiautomatic weapons - Wills, Chuck (Skyhorse Publishing, 2014)
The Illustrated History of Guns is a comprehensive look at the often deadly, sometimes surprising, always fascinating tools of battle. More than three hundred photographs of an eclectic mix of weapons were specially commissioned from the 8,000-piece collection of the Berman Museum of World History. Spanning the globe and hundreds of years, they include the traveling pistols of Confederate president Jefferson Davis and Heinrich Himmler's rifle. A variety of rare weapons of espionage and combination curiosa makes the collection of special interest to even the most seasoned weaponry connoisseur. The extraordinary weapons from the Berman Museum of World History are collected in this one-of-a-kind volume. Within these pages, you'll find weapons owned by Benito Mussolini, Belle Starr, Hermann Goering, Napoleon III, and Kaiser Wilhelm. Chuck Wills offers historical perspective of the people, places, and times important to the development of firearms, with special features that illuminate such topics as the Civil War and trench warfare. The rare and wonderful pieces collected here and their commentary offer something for the history buff, cultural anthropologist, and weapons enthusiast alike.